Morphological Evolution of High-Voltage Spinel LiNi0.5Mn1.5O4 Cathode Materials for Lithium-Ion Batteries: The Critical Effects of Surface Orientations and Particle Size - Liu, Haidong; Wang, Jun; Zhang, Xiaofei; Zhou, Dong; Qi, Xin; Qiu, Bao; Fang, Jianhui; Kloepsch, Richard; Schumacher, Gerhard; Liu, Zhaoping; Li, Jie (ACS applied materials & interfaces, 2016)
An evolution panorama of morphology and surface orientation of high-voltage spinel LiNi0.5Mn1.5O4 cathode materials synthesized by the combination of the microwave-assisted hydrothermal technique and a postcalcination process is presented. Nanoparticles, octahedral and truncated octahedral particles with different preferential growth of surface orientations are obtained. The structures of different materials are studied by X-ray diffraction (XRD), Raman spectroscopy, X-ray absorption near edge spectroscopy (XANES), and transmission electron microscopy (TEM). The influence of various morphologies (including surface orientations and particle size) on kinetic parameters, such as electronic conductivity and Li+ diffusion coefficients, are investigated as well. Moreover, electrochemical measurements indicate that the morphological differences result in divergent rate capabilities and cycling performances. They reveal that appropriate surface-tailoring can satisfy simultaneously the compatibility of power capability and long cycle life. The morphology design for optimizing Li+ transport and interfacial stability is very important for high-voltage spinel material. Overall, the crystal chemistry, kinetics and electrochemical performance of the present study on various morphologies of LiNi0.5Mn1.5O4 spinel materials have implications for understanding the complex impacts of electrode interface and electrolyte and rational design of rechargeable electrode materials for lithium-ion batteries. The outstanding performance of our truncated octahedral LiNi0.5Mn1.5O4 materials makes them promising as cathode materials to develop long-life, high energy and high power lithium-ion batteries.